Design and Implementation of an Android Application for Management of Events - Navya, K; Shirisha, N; Soumya, G; Divya Jyothi, G (International Journal of Engineering and Technology, 2018)
This paper presents the design and implementation of an android application for managing various events. The software is supported to eliminate and in some cases reduce the hardships faced by any event organizer. It is mainly designed to carry out the operations smoothly and efficiently. Users will have to create accounts with their credentials. This software provides a user-friendly interface which allows the clients to contact service providers effectively. It also provides a note-keeping service which gives reminders time to time to the busy organizer. It makes it easy for the user and the clients to store their past expenses and events. This software makes the event organizer plan his event more strategically and provides better services to the clients.Â Â Â